The virulence contribution of the CFEM family genes of Beauveria bassiana is closely influenced by the external iron environment - Xu Zhang; Guang Wang; Bin Chen; YueJin Peng (Microbiology Spectrum)
ABSTRACT The common in fungal extracellular membrane (CFEM) domain proteins represent characteristic fungal extracellular membrane proteins. The entomopathogenic fungus Beauveria bassiana contains 12 CFEM domain proteins involved in the generation of iron hunger response. However, many BbCFEM genes that infect insects do not promote fungal virulence. In this study, we systematically assessed the role of the BbCFEM family in fungal virulence under moderate iron concentrations and severe iron starvation (0.4 mM BPS) induced by body wall infection and injection infection. The results showed that the BbCFEM family members have different functions based on virulence, which is directly affected by external iron levels. Quantitative real-time reverse-transcription polymerase chain reaction preliminarily demonstrated that deletion of BbCFEM family genes significantly increased the expression levels of other family members. The increased expression levels compensated for the gene damage induced by the deletion of BbMFEM genes. In addition, the results showed that the BbCFEM gene participates in the initiation of fungal responses to cell wall stress and oxidative stress. These findings reveal the evolutionary strategies employed by pathogenic fungi to adapt to the environment and population reproduction. This study expands our understanding of the mechanism of this gene family of entomopathogenic fungi in infecting pests.IMPORTANCEThe common in fungal extracellular membrane (CFEM) domain is a fungal extracellular membrane protein that can trap heme, which assists in fungal infection and colonization. Beauveria bassiana is an entomopathogenic fungus that is widely used to control pests. We systematically assessed the contribution of the BbCFEM family to B. bassiana’s virulence under severe iron starvation and B. bassiana’s growth and stress resistance under moderate iron levels. We found that the BbCFEM family members have different functions based on virulence with severe iron starvation, which also plays an important role in fungal responses to cell wall stress and oxidative stress. This study provides new insights into the genetic families of entomopathogenic fungi and the mechanisms by which they infect pests.